CONTINUING PROFESSIONAL DEVELOPMENT (CPD) FOR THE SOCIAL WORK PROFESSION IN SOUTH AFRICA - Lombard, Antoinette; Pruis, Santie; Grobbelaar, Margaret; Mhlanga, Dudu (Social Work/Maatskaplike Werk, 2010)
The South African Council for Social Service Professions (SACSSP) took a principled decision during a meeting on 23 and 24 July 2003 to adopt continuing professional development (CPD) as a requirement for registration to practise. This decision has positioned and committed social service professions amongst many other professions, nationally and internationally, to continue their professional development through “the systematic maintenance and improvement of knowledge, skills and competence throughout a professional’s working life” (Butler, 2003:18).